The Influence of Husband Support and Information Sources on Cervical Cancer Screening Behavior - Ilham Salam; Sudirham Sudirham; Tika Bela Sari (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: Cervical cancer is still the